Ktahkomiq: Language as a Territory - Burelle, Julie (Percées)

(untitled) (Société québécoise d'études théâtrales (SQET), 2023)
This article discusses the performance Ktahkomiq (“Territory”) created in 2017 by Dave Jenniss and Ivanie Aubin-Malo with the dramaturgical support of Catherine Joncas. I examine the creative process developed by the artists to explore a long-standing conflict dividing their community without minimizing its irreconcilable dimensions. In particular, I attend to the moments of refusal and reconciliation that shape the performance as well as the role that the Wolastoqey language played in creating a shared territory for the artists.